Systemic lupus erythematosus complicated by severe Guillain-Barré syndrome: case report and literature review - He, Lifeng; Zhang, Zengrui; Tan, Ying (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a heterogeneous chronic autoimmune disease characterized by immune-mediated multiple organ injuries in the setting of autoimmunity to nuclear antigens. In rare cases, it can complicated by the damage of peripheral nervous system, manifesting as Guillain–Barré syndrome (GBS). Severe GBS as the initial presentation is highly infrequent and associated with high disability and mortality rates, highlighting the importance of early detection, diagnosis, and treatment. Herein, we reported a successfully treated case of severe SLE-GBS in a 38-year-old male. Furthermore, we summarize the clinical characteristics of severe SLE-GBS reported thus far and propose the possibility of using medium-to-high dose corticosteroids in the acute progression stage of SLE-GBS. This report provides valuable insights for the analysis of disease characteristics and guidance for diagnosis and treatment of such cases.